Association Of Hyperkalemia With T-Wave Changes In Chronic Kidney Disease Patients Versus Hemodialysis Patients. (Pakistan Journal of Kidney Diseases, 2024)
Hemodialysis (HD) patients often face hyperkalemia due to various reasons. Level of hyperkalemia and ECG changes may be discordant among HD patients in a significant number of patients. This study was conducted to investigate whether or not there is a unique ECG characteristic that predicts hyperkalemia in individuals with chronic kidney disease (CKD).OBJECTIVE: To determine an association between hyperkalemia (raised serum potassium) and T- (atypical T-wave) changes on ECG in CKD patients versus HD patients.METHODOLOGY200 patients on HD and CKD 4 & 5 not on HD, fulfiling the inclusion criteria were enrolled in the study. Sampleing for seum potassium levels were done and ECG obtained.RESULTSMean age in HD and CKD groups respectivley was 51.46 ± 26.96 and 56.16 ± 21.68 years. In HD group there were 61 males and 39 females whereas in CKD group there were 57 males and 43 females. Mean serum potassium levels were 5.20 ± 0.85 (mEq/L) in HD group whereas in CKD group mean serum potassium levels were 5.50 ± 0.62 (mEq/L). The mean T-wave duration in HD group was 168.01 ± 2.94 (msec), while in CKD group the mean T-wave duration was 173.76 ± 2.33 (msec). In HD group Pearson correlation coefficient was -0.779 with a P -value of 0.000, whereas in CKD group Pearson correlation coefficient was -0.02 with P -value was 0.985.CONCLUSIONIn our study, there was a negative correlation between serum K+ levels and duration of T-wave in patients on maintenance HD. T
Keywords: chronic kidney disease; hemodialysis; hyperkalemia; ECG; t wave; sudden cardiac death; arrythmia